Lactic acid bacteria used as preservative in fresh feed for marine shrimp maturation - Vieira, Genyess Ribeiro Arthur da Silva; Soares, Mariana; Ramírez, Norha Constanza Bolívar; Schleder, Delano Dias; Silva, Bruno Corrêa da; Mouriño, José Luiz Pedreira; Andreatta, Edemar Roberto; Vieira, Felipe do Nascimento (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of Lactobacillus plantarum on the preservation of fresh mussels and its effect on the attractiveness, consumption, and midgut bacterial microbiota of Pacific white shrimp broodstock. The experiment evaluated mussels stored with L. plantarum at 4°C. The controls were: mussels stored at ‑18°C without L. plantarum; mussels stored at ‑18°C with L. plantarum; and mussels stored at 4°C without L. plantarum. Microbiological analyses on mussels were performed on days 1, 7, 15, 30, 45, and 60 after processing. Additionally, mussels preserved with L. plantarum and stored at 4°C, and mussels stored at ‑18°C without L. plantarum were evaluated after 15 days for attractiveness, consumption, and midgut bacterial microbiota of shrimps. Mussels preserved with L. plantarum showed higher lactic acid bacteria counts and lower counts of Vibrio spp., as well as of total heterotrophic bacteria, after 60 days of storage. No differences were observed for attractiveness or consumption between treatments. The bacterial microbiota of midgut in shrimp fed mussels preserved with L. plantarum showed higher lactic acid bacteria count and lower Vibrio spp. The use of L. plantarum inhibits Vibrio spp. and preserves feed without changing attractiveness or consumption for shrimp.